Analysis on Human Rights Enforcement by Adopting UDHR inIndonesia and Malaysia - Zahira, Shafa Dhia; Mujaddid, Ahmad; Hussin, Mutia Hariati (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2021)
Human Rights is one of the major priorities which continue to be pursued by the Association of Southeast Asian Nations (ASEAN). This is manifested by the commitment of member countries to establish the ASEAN Intergovernmental Commission on Human Rights in 2009 which resulted in the ASEAN Human Rights Declaration in mid-2012. In promoting human rights, many countries have adopted the values of the Universal Declaration of Human Rights (UDHR) which is the main foundation for freedom and equality. This research found that Indonesia and Malaysia both have already had various UDHR values in their constitution and even implement them in the foreign policy of their respective countries. By utilizing constructivism theoretical approach through a qualitative method, where literature study is conducted by gathering information through books, reports, news articles and journal articles. Our analysis finds that there are significant differences in the human rights systems implementation and mechanisms developed by each ASEAN country, including in Indonesia and Malaysia. Therefore, the authors suggest using a sustainable constructive approach in adopting UDHR values